Irrigation development in the Vietnamese Mekong Delta: towards polycentric water governance? - Hoanh, Chu Thai; Suhardiman, Diana; Anh, L.T. (Baltzer Science Publishers, 2014)
Vietnam’s irrigation development policy directions are divided between the objective to continue increasing rice production through agricultural intensification and to improve farmer’s livelihoods through crop diversification and integrated farming. While the first objective requires the construction of new large-scale irrigation system in deeply flooded area of the Vietnamese Mekong River Delta, the latter demands the modification in management of existing irrigation physical infrastructure for non-rice crops, in particular brackish aquaculture in the coastal zones. This article looks at Vietnam’s irrigation policy formulation processes in the last three and half decades in relation to the idea of polycentric governance. It discusses the current shortcomings and potential role of polycentric governance networks to capture stakeholders’ interests at multiple governance levels essential for future policy development. It partially sheds light on the dark side of water governance, bringing to light the fragmented polycentric decision-making processes in Vietnam’s irrigation development policies.